THE THE WORD CHAIN TEST: THE NORMATIVE DATA FOR STUDENTS FROM GRADES 1 TO 9 - Trinīte, Baiba; Tūbele, Sarmīte (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The Word Chain Test (WCT) is a rapid screening procedure that appears to identify primary and secondary school students with poor silent word decoding abilities. The WCT was adapted to the Latvian language in 2003. However, norms for the test had yet to be established. The study is aimed to develop the WCT normative data set for students from grades 1 to 9. Students from grades 1 to 9 (N = 4476) representing all geographical regions of Latvia, urban and country territories completed the WCT that included two subtests – letter chains and word chains. The descriptive statistic parameters were estimated for each grade. The results demonstrated statistically significant correlations between scores of word and letter chains and the age of students. The statistically significant differences in the average scores of letter and word chains were found between boys and girls. The scores of letter and word chains were scaled separately for boys and girls by grade using a standard nine-point scale. The 5th, 7th, and 16th percentiles were estimated for diagnostic purposes. The developed WCT normative data set allows the examiner to assess students' visual-spatial and word-decoding skills. Future studies should continue the standardization procedures by determining the convergent and clinical validity of the WCT.